Jihad Against Drug Mafias: A Case Study of Community Collective Movement at Ujoeng Pacu, Lhokseumawe-Aceh - Nirzalin, Nirzalin; Nazaruddin, M (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
Collective movement for drug eradication organized by the community was proved to be more effective in stopping the drug trafficking compared to the security approaches organized by the state apparatus (government). Based on the case study of communitys collective movement in the village of Ujoeng Pacu Lhokseumawe, this artilce is intended to show the complex phenomena of genealogy and the dynamics of the collective movement of the community in fighting the drug mafias. Using the Perspective of Tilly Collective Movement and the Method of Phenomenolgy, the study found that the jihad collective movement on the drug eradication caried out by the community of Ujong Pacu was motivated by the rigging relationship among theological unrest, social and economical security, and concerns about the future generations. The consideration of the drug as the only trigger of any Â immoral (ma maksiet) activities towards Allah Almighty has made the flow of this movement not only significant to the social movement but also to theological movement (jihad). Due to its interpretation as a religious movement, the moral of the drug eradication movement was not deterred despite the various threats and the terror bombing as an act of counter-attack from the drug mafias occured repeatedly in theUjoeng Pacuâs community.